2017
DOI: 10.15244/pjoes/69144
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Water Permeation through the Soil-Rock Mixture in Underground Engineering

Abstract: Groundwater inrush within faults is an important issue in underground engineering. The process of water permeation through the soil-rock mixture has been numerically investigated. The simulated soil-rock mixture was presented with rock blocks, and filled with selected types of soil particles. The Euler-Euler method was employed with multiphase interaction. Meanwhile, the filling soil was assumed to be Bingham fluid with additional user-defined function. Then the detailed evolutions of water permeation through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Under high geo-stress, high groundwater pressure is prone to cause engineering geological disasters, such as water inrush. It seriously affects the construction progress and personnel safety for underground rock engineering [3]. The excavation of underground engineering, in fact, is the triaxial loading and unloading processes of the surrounding rock masses.…”
Section: Introductionmentioning
confidence: 99%
“…Under high geo-stress, high groundwater pressure is prone to cause engineering geological disasters, such as water inrush. It seriously affects the construction progress and personnel safety for underground rock engineering [3]. The excavation of underground engineering, in fact, is the triaxial loading and unloading processes of the surrounding rock masses.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a numerical simulation is used to study the migration of water in three different structural pores of the fractured rock mass, and the seepage-flow transformation mechanism of the fillings in the pore of the fractured rock mass is revealed. e simulation model of the soil-rock mixture is based on previous studies [4,39,40], as shown in Figure 1. e filling structure can be regarded as consisting of the fixed particles phase (soil skeleton), the movable particles phase, and the water phase.…”
Section: Fluid-solid Coupling Model Of Granularmentioning
confidence: 99%
“…To quantitatively understand the impact of various influencing factors on the infiltration instability of filling media, a two-dimensional finite element model was established by using the Fluent software [40]. Each of the three structural models is 1 m long and 0.5 m wide.…”
Section: Establishment and Solution Of Numerical Analysis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A great amount of research has been devoted to the catastrophic evolution process of water inrush [2][3][4] and the risk assessment of water inrush, while the main focus has been on the risk of floor water inrush in coal mines [5][6]. Many new methods have been put forward to predict water inrush, such as the support vector machine [7], BP neural network and DS theory [8], geographic information system [9], a secondary fuzzy comprehensive evaluation system [10], and four-zone theory [11], as well as fault tree analysis [12].…”
Section: Introductionmentioning
confidence: 99%